Strategi Pembukuan dan Pemasaran untuk Meningkatkan Daya Saing dan Penjualan Usaha Warung Sembako Ibu Anik - Kholilah Sajidah Kholilah; Nugraeni Nugraeni (PADMA, 2025)
This community service activity focused on improving the competitiveness and sales of Ibu Anik's Grocery Store, a local MSME facing challenges related to promotion and irregular bookkeeping. The goal was to help business owners understand and implement a simple bookkeeping system and effective digital-based marketing strategies to make their business more efficient and widely recognized. The methods used included problem identification, activity planning, theoretical and practical training on bookkeeping and online promotion, along with monitoring and evaluation. The results of the activity demonstrated an increase in the ability of business owners to accurately record daily transactions, understand cash flow, and begin utilizing social media as a promotional tool. The tangible impact was seen in increased managerial awareness and the potential for better sales in the future.